Analisis Maqashid Syariah Tentang Jual Baju Bekas Impor (Thrift): Studi Kasus Second Branded A’iki di Desa Haurpanggung Kecamatan Tarogong Kidul Kabupaten Garut - Gaussian, Gini; Fahira, Luthfia Putri (Jurnal Hukum Ekonomi Syariah, 2024)
Buying and selling is an agreement to exchange objects or goods that have value voluntarily between two parties, where one party sells the goods and the other party buys them in accordance with an agreement or regulation that has been confirmed by the sharia and agreed upon. Apart from the agreement between the two parties, in carrying out the sale and purchase agreement we must know whether the sale and purchase being carried out is contrary to the maqashid sharia or not, because it is feared that it is contrary to the maqashid sharia. So a problem formulation emerges: what is the system for buying and selling used imported clothes (thrift) in second branded a'iki and what is the maqashid sharia analysis regarding buying and selling used imported clothes (thrift) in second branded a'iki. The aim of this research is to find out the system of buying and selling used imported clothes (thrift) in second branded a'iki. and to find out the maqashid sharia analysis by buying and selling imported used clothes (thrift) at second branded a'iki. The research method carried out by researchers is field research with a qualitative approach, namely descriptive and analytical research. The result of this research is that buying and selling thrifts is contrary to maintaining religion and maintaining the soul.  Keywords: Maqashid syaria, Buying and Selling and Imported     Used Clothes (thrift)